Supply Chain Management Strategy Research Quantitative Analysis: Comparing of Smart-PLS and SPSS Results - Istimaroh; Idham Chalid; Bambang Setiaji; Noor Aslinda Abu Seman (Krisnadwipayana International Journal of Management Studies, 2024)
Many researchers are unsure which software to use for quantitative research data analysis because there is no research comparing different software options. This study aims to compare the results of using Smart-PLS and SPSS software for analyzing quantitative data in the field of supply chain management. The study analyzed data from 231 respondents using questionnaires with three variables: lean supply chain strategy, agile supply chain strategy, and sustainable performance. The analysis focused on hypothesis testing and regression analysis, which measures the influence of independent variables on dependent variables. The study found that both Smart-PLS and SPSS software produced significant results in terms of p-value, t-value, determination value, and correlation value. This research is unique because it provides a comparative analysis of Smart-PLS and SPSS software.